El gran Gatsby - Fitzgerald, F. Scott (Francis Scott), 1896-1940 (Clásicos de la literatura (Akal Editor), 2015)
In 1920s Long Island, a mysterious American millionaire's efforts to recapture the sweetheart of his youth result in tragedy.